The Effect of Using Quizlet on Students' Vocabulary Mastery - Ramadani, Iftia Asri; Oktarini, Widya; Devanti, Yeni Mardiyana (Jurnal Pendidikan Tambusai, 2024)
In the 21st century, using electronic flashcard media is an option educators in Indonesia consider to provide variety in learning using existing technology. The problem of this research is "Is there any significant effect of Quizlet on students' vocabulary mastery in SMA Muhammadiyah 3 Jember in 2023/2024 academic year?" and the objective of this research referring to the research problem is to find out the effect of Quizlet on students' vocabulary mastery on SMA Muhammadiyah 3 Jember in 2023/2024 academic year. Based on the research problem and the objective of the research, the hypothesis is described as follows: There is an effect of using Quizlet on students' vocabulary mastery in SMA Muhammadiyah 3 Jember in the 2023/2024 academic year. This study aims to determine whether or not utilizing Quizlet to learn reading impacts students' vocabulary in grade 11 at SMA Muhammadiyah 3 Jember. The pre-experimental research approach was employed in this study to determine the effect on research subjects before and after treatment. This research shows the significance of students or subjects in the post-test scores compared to students' scores during the pre-test. Based on the research, Quizlet combined with reading skills affects students' vocabulary at SMA Muhammadiyah 3 Jember in the 2023/2024 academic year.